STUDY ON FUNCTIONS OF CODE SWITCHING IN ENGLISH LANGUAGE CLASSROOM - Fatanah Wachdin (The Ellite of Unira, 2020)
Code switching occurs in bilingual and multilingual community when a person switches from one language, variety, or dialect to another one. People can do code switching in any kinds of situation and domain. Social context influences someone to convey information by alternating different codes for communication. Code switching also occurs in the process of teaching and learning in the classroom by lecturers and students because they speak with more than one language. They can change or mix the language when they have the same perception of things or something that is being communicated.The researcher conducted this research to shows the kinds and the functions of code switching that used by English department student at Madura University, especially for seventh semester students when they were teaching practice in micro teaching. Because as candidates of teacher, student of seventh semester must follow micro teaching before they follow teaching practice program.This research is qualitative research by using descriptive case study. The data were collected by video recording while the participant of study having teaching practice in micro teaching. The result of this research indicate that most of the participant of study use situational code switching, and only some participant use metaphorical code switching. It means that teaching English process used Indonesian – English code switching. And the most functions that participant use is explanation function.The researcher also expected that this research will be able to help the readers know and understand about phenomena of code switching that occurs in bilingual or multilingual conversation, and to be useful for next researcher to conduct more comprehensive and more detail study especially relating about code switching.